A comparative study of the life histories of the sister species, Pseudobarbus afer and Pseudobarbus asper, in the Gamtoos River system, South Africa - Cambray, James Alfred (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1993)
This thesis explores the biology, ecology, and life-history styles of two closely-related redfin minnows, Pseudobarbus afer and P. asper (pisces; Cyprinidae), which both occur in the Gamtoos River system of South Africa. Five of the seven species of flexible-rayed redfin minnows are in the South African Red Data Book - Fishes. This investigation was designed to provide the data which would enable conservation authorities to manage the remaining populations of the Pseudobarbus species. A thorough understanding of the Gamtoos River system was necessary to properly interpret the findings of this study. The palaeo river systems and the changing climates since the break-up of Gondwanaland are discussed so that the present day environments could be considered as well as the past environmental changes. P. afer and P. asper occur in the Gamtoos River system with no physical barrier separating the two species. P. afer only occurs in the clear mountain streams of the Cape Fold Mountain Belt whereas P. asper occurs in the highly saline and turbid Karoo section of the system. P. afer were found to be the more precocial form of the sister species. They had bigger eggs, lower relative fecundity, shorter breeding season, lower gonadosomatic indices, larger first feeding larval fish, matured later and had a longer life-span than did P. asper, which had more altricial life-history attributes. They differ in their tradeoffs with P. asper devoting more resources earlier to reproduction and having a shorter lifespan. The improvement in the one aspect of fitness (early maturity) leads to the deterioration in another, namely lifespan. Both species undertake breeding migrations to riffle areas where they spawn in mid-channel immediately above a pool after an increase in water flow. P. afer and P. asper are non-guarders of their non-adhesive eggs and young, open substrate spawners on coarse substrates (rocks) and have photophobic free embryos. The breeding season is shorter for P. afer whereas P. asper can spawn as late as April and impoundment releases can induce them to spawn. A study of comparative neuroecology revealed that of the four groups of fish analyzed (males and females of both species) male P. afer had the largest brains, especially the optic lobes and cerebellum. P. asper females had the smallest brains. No neural compensation in the external gustatory centre, the facial lobe, was found for P. asper inhabiting the turbid waters. P. afer also had significantly larger eyes and longer barbels. P. afer males were also found to have the highest density and largest nuptial tubercles as well as the most pronounced breeding colouration. It was concluded that P. asper is the more derived of the sister species pair with regard to life-history attributes. It is further suggested that investment per offspring is important in determining the life-history trajectories. Paedomorphosis has occurred and by this mechanism variability has been restored to the redfin minnows in the Groot River which enables them to survive in the highly variable, intermittent Karoo stream. The more precocial P. afer do not require this variability in the more constant and predictable environment of the Wit River.
Keywords: Barbus -- Life cycles; Barbus -- Ecology -- South Africa -- Gamtoos River; Cyprinidae -- Life cycles; Cyprinidae -- Ecology -- South Africa -- Gamtoos River; Minnows -- Life cycles; Minnows -- Ecology -- South Africa -- Gamtoos River